ANALISIS PUTUSAN PENGADILAN TINGGI NOMOR: 5/PDT/2018/PT.PBR TENTANG PERBUATAN MELAWAN HUKUM BERKAITAN DENGAN REKLAMASI LAHAN PASCA TAMBANG - Eisano, Sapna Keryn; Tamsil, Tamsil (Universitas Negeri Surabaya, 2019)
Abstract Case number 5/Pdt/2018/Pn.Pbr is evidence that there are still companies that do not carry out post-mining reclamation and the government does not carry out supervision in accordance with statutory regulations. PT Riau Bara Harum as the holder of IUP and IPPKH Limited Production Forest Areas in Riau left the mining area without doing any post-mining reclamation, making the judge in decision number 22/Pdt.G-LH/2016/Pn.Rgt decide PT Riau Bara Harum and the Ministry of Energy and Mineral Resources have violated the law and punished the Ministry of Energy and Mineral Resources for reclamation of the object of dispute. The Ministry of Energy and Mineral Resources then made an appeal to the High Court with case Number 5/Pdt/2018/Pt.PBR, in which the Panel of High Judges upheld Decision Number 22/Pdt.G-LH/2016/PN.Rgt. This research is a normative legal research, the approach used is the law, case and conception approach. The research was conducted with primary and secondary legal materials, and the collection of legal materials used literature study. The results of this study are to determine the judge's considerations and the legal consequences of the judge's considerations. Keywords: post-mining reclamation, supervision, coal mining